Mathematical modeling for thin layer sun drying of ginger (Zingiber officinale Rosc.) - R Visvanathan, E Jayashree, (Journal of Spices and Aromatic Crops, 2013)
Trials on drying of ginger were conducted during the month of April, 2009 at Agricultural Engineering College and Research Institute, Coimbatore (Tamil Nadu). Ginger rhizomes were mechanically washed, partially peeled, spread in single layer on cemented yard and dried from initial moisture of 594.01% (d.b.) (dry basis) to a final moisture content value of 9.82% (d.b.). Drying of ginger was completed in eight days. Drying characteristics curves, showed no constant rate period and all the drying process occurred in the falling rate period. Thin layer modeling of drying data showed that diffusion approximation model best described the drying process. The effective moisture diffusivity for drying of ginger was calculated as 1.91 × 10-7 m2 s-1. Sun dried ginger rhizomes were evaluated for its quality and it was found that the essential oil, oleoresin, moisture and crude fibre contents were 2.0%, 4.6%, 9.82% and 2.5%, respectively